2022
DOI: 10.1186/s12960-022-00763-8
|View full text |Cite
|
Sign up to set email alerts
|

Provision of injectable contraceptives by community health workers in sub-Saharan Africa: a systematic review of safety, acceptability and effectiveness

Abstract: Background Injectable contraceptives are the most popular method of contraception in sub-Saharan Africa (SSA), but their availability in clinical settings has been severely limited, despite the scarcity of health care providers and limited access to health facilities. WHO and USAID have endorsed the community-based distribution of injectable contraceptives as a promising option for improving access to family planning services and expanding the method mix for women who want to limit the number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The low rate of EBF is comparable to the national average found in 2017 (42%) [ 6 ], 2018 (46%) [ 14 ] and 2019 (41%) [ 15 ]. In contrast, the median duration of EBF, i.e.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The low rate of EBF is comparable to the national average found in 2017 (42%) [ 6 ], 2018 (46%) [ 14 ] and 2019 (41%) [ 15 ]. In contrast, the median duration of EBF, i.e.…”
Section: Discussionmentioning
confidence: 56%
“…In contrast, the median duration of EBF, i.e. the point at which half of the children stopped being exclusively breastfed, is higher than those estimated in 2017 and 2018; at 2 (DHS 2017) and 2.6 months (DHS 2018) [ 6 , 14 ] respectively. This difference could be explained by the methodology used.…”
Section: Discussionmentioning
confidence: 99%
“…Task shifting and community‐based provision of the injectable has been piloted and widely implemented in a variety of settings 20–24 . A systematic review found that across studies conducted in African countries, provision of the injectable by CHWs was generally safe, acceptable, and effective, but the authors noted a need for more high quality research, including qualitative studies 25 . A pilot study of CHV provision of the injectable was conducted in Kenya in 2009–2010 and contributed to the policy change to broadly allow these health workers to provide the injectable in hard‐to‐reach areas 26 .…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22][23][24] A systematic review found that across studies conducted in African countries, provision of the injectable by CHWs was generally safe, acceptable, and effective, but the authors noted a need for more high quality research, including qualitative studies. 25 A pilot study of CHV provision of the injectable was conducted in Kenya in 2009-2010 and contributed to the policy change to broadly allow these health workers to provide the injectable in hard-to-reach areas. 26 While we found no significant association with overall provision of the injectable, it is possible that as a result of the intervention some people shifted from obtaining the injectable from a health facility to obtaining it from a CHEW.…”
Section: Concern Example Quotationmentioning
confidence: 99%
“…Effectiveness of task shifting and sharing - evidence from the literature: task shifting and sharing have been successfully used to improve health in various settings and times, including the COVID-19 pandemic, to address global health workforce shortages and inadequate access to care for critical health issues [ 4 , 14 - 17 ]. Some studies have shown that task sharing and shifting are efficient and effective methods for assisting healthcare workers in completing duties not previously within their purview and increasing human resource for health (HRH) and quality outcomes [ 14 - 18 ]. For instance, Amani et al .…”
Section: Essaymentioning
confidence: 99%